Stalemate for the financialization of climate policy - Ève Chiapello (economic sociology_the european electronic newsletter, 2020)
The aim of this article is to suggest certain avenues of reflection on the growing importance of finance when imagining a new stage in environmental policies that systemically accompanies the financialization of capitalism. We then show that the alignment of green finance with the economic-political regime from which it emerged condemns it, for the time being, to impotence. Yet criticism might result in the reform effort shifting towards more ambitious proposals.
Keywords: 300